Leadership reflections : how to create and sustain reforms in children and family services - Williams-Isom, Anne, 1964- (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"This book series will share lessons learned from experts in the field of child welfare, education and partnering with communities in order to promote the well being of children. It is more important than ever to share best practices with emerging leaders in the social services and education fields. Leaders and students need to understand the practical application of policies and theories. This book project will address the recurring theme of leadership development, collaboration with communities and the importance of diverse teams to bring about systemic change and large scale reforms. The books can be used as a guide. They will provide important insights and tools that can be used by a diverse group of leaders and students in the social services and education fields. Each book in the series will provide a unique view of the topic because it is told by practitioners, leaders and policymakers who have first hand knowledge of the topic. The theme of leadership development and racial justice and equity will also recur throughout the series. Recent events in this country are exposing more people to the disparities and inequities that exist for black and brown people. These disparities have to be addressed with a variety of different strategies. This book series addresses one such area; the urgent need to reduce these disparities and dismantle the systemic obstacles that continue to stand in the way of families, children and communities thriving"--